Pre- and Post-diagnosis Diabetes as a Risk Factor for All-Cause and Cancer-Specific Mortality in Breast, Prostate, and Colorectal Cancer Survivors: a Prospective Cohort Study - Tao, Huan; O'Neil, Adrienne; Choi, Yunseon; Wang, Wei; Wang, Junfeng; Wang, Yafeng; Jia, Yongqian; Chen, Xiong (Frontiers in Endocrinology, 2020)
Objective: The relationship between diabetes and all- and cause-specific mortality in individuals with common cancers (breast, colorectal, and prostate) remains both under-researched and poorly understood. Methods: Cancer survivors (N = 37,993) from the National Health Interview Survey with linked data retrieved from the National Death Index served as our study participants. Cox proportional-hazards models were used to assess associations between pre- and post-diabetes and all-cause and cause-specific mortality. Results: Over a median follow-up period of 13 years, 2,350 all-cause, 698 cancer, and 506 CVD deaths occurred. Among all cancer survivors, patients with diabetes had greater risk of: all-cause mortality [hazard ratio (HR) 1.35, 95% CI = 1.27–1.43], cancer-specific mortality (HR: 1.14, 95% CI = 1.03–1.27), CVD mortality (HR: 1.36, 95% CI = 1.18–1.55), diabetes related mortality (HR: 17.18, 95% CI = 11.51–25.64), and kidney disease mortality (HR: 2.51, 95% CI = 1.65–3.82), compared with individuals without diabetes. The risk of all-cause mortality was also higher amongst those with diabetes and specific types of cancer: breast cancer (HR: 1.28, 95% CI = 1.12–1.48), prostate cancer (HR: 1.20, 95% CI = 1.03–1.39), and colorectal cancer (HR: 1.29, 95% CI = 1.10–1.50). Diabetes increased the risk of cancer-specific mortality among colorectal cancer survivors (HR: 1.36, 95% CI = 1.04–1.78) compared to those without diabetes. Diabetes was associated with higher risk of diabetes-related mortality when compared to non-diabetic breast (HR: 9.20, 95% CI = 3.60–23.53), prostate (HR: 18.36, 95% CI = 6.01–56.11), and colorectal cancer survivors (HR: 12.18, 95% CI = 4.17–35.58). Both pre- and post-diagnosis diabetes increased the risk of all-cause mortality among all cancer survivors. Cancer survivors with diabetes had similar risk of all-cause and CVD mortality during the second 5 years of diabetes and above 10 years of diabetes as compared to non-diabetic patients. Conclusions: Diabetes increased the risk of all-cause mortality among breast, prostate, and colorectal cancer survivors, not for pre- or post-diagnosis diabetes. Greater attention on diabetes management is warranted in cancer survivors with diabetes.